حقوق الإنسان في الديانات القديمة واليهودية والإسلام: قضايا ونماذج - شكرود, فرحانة (جامعة سيدي محمد بن عبد الله، كلية الآداب و العلوم الانسانية-سايس-فاس, 2019)
Title of the study: Human rights in ancient religions as well as Judaism and Islam: Cases and examples The aims of the study: This study aims at tracing human rights in ancient religions and the two religions of Judaism and Islam through how these civilisations cherished these rights and some violations. It is an attempt to trace the foundations of human rights and collect the scattered ancient and contemporary sources to facilitate academic research for interested researchers. It presents the similarities and differences between Judaism and Islam not for the sake of enhancing violence but rather for mutual encounter. Methodology: this study falls into personal categorization of human rights in order to employ it when studying human rights in the two religions. Since there is no specific categorization that would assist researchers, this study fill in this gap. This categorizations is as follows:  Fundamental Rights  lno oson c c monocE rights  siEuircE c c loEouoncE rotlum  schcEu r nm rotlum In this study, I opted for these approaches to answer the problematic question of the research: Descriptive, deductive , Historic and comparative approaches. The main results : • Ancient East laws were the first legislations that were set to organize the societies; and they were based on a group of customs and traditions and norms wide spread then. • Judaism calls for human rights through the Old Testament and Talmud for the sake of establishing a just society; and these rights were implemented in the Ten Commandments. • The two religions have focused on legislations mainly Islam since it is the last religion; and the comparison between both of them shows common as well as different features because Islam as a more widely and holistic view concerning recognizing the other religions and calling for affection and rejecting fundamentalism and discrimination which is dissimilar to Judaism that has an inclusive view. These Islamic features are to preserve the individual rights and implement duties for a stable community.
Keywords: Human right; Ancient religion; Judaism; Islam.